Mechanism and detection of oscillatory flow in a supersonic cascade. (May 2021) - Wang, Ziao; Chang, Juntao; Wu, Guangwei; Hou, Wenxin
Abstract: The throttling process in a supersonic cascade is investigated in a free-jet wind tunnel at Mach 2.4. High-speed schlieren imaging and high-resonance frequency pressure measurements are used to capture the flow features. A flap is placed at the channel exit to choke the flow linearly. In the throttling process before the onset of oscillatory flow, the shock train leading shock leads to large area of flow separation near the suction surface and high total pressure loss. The oscillatory flow is triggered by the expansion of the flow separation induced by the impingement of the shock train leading shock onto the suction surface, which belongs to the Dailey criterion. The alarm is triggered during oscillatory flow detection, based on the pressure data at the optimal S5 transducer, either before the large-amplitude pressure fluctuation begins or after it ends. Comparing with other algorithms, the derivative-based algorithm has no data to be stored and no expensive calculation is the best technique for detection. To adjust the alarm margin, three detection points are set upstream of the S5 transducer and detection is performed based on the schlieren images. All algorithms detect the sudden drop in light intensity caused by the arrival of the shock train leading shock at the detection location. The alarm margin is the largest at point C, which is farthest from the suction surface tip, and smallest at point A, which is closest to the suction surface tip. Highlights: Throttling process of a supersonic cascade was studied experimentally. More flow field variables distributions were complemented by numerical simulation. The mechanism of oscillatory flow was revealed. The oscillatory flow was detected based on pressure and schlieren images.